We reject then accept: The rhetoric of defeat in Anies-Muhaimin's post-2024 presidential election - Anshori, Mahfud (Program Studi Ilmu Komunikasi, 2025)
This study aims to analyse the defeat speeches of Anies Baswedan and Muhaimin Iskandar following their loss in the 2024 Indonesian presidential election. Employing Aristotelian rhetorical theory, it examines six speeches delivered between February and March 2024 to identify the rhetorical patterns and strategies used. The findings indicate that these speeches were not merely formal acknowledgments of defeat but carefully crafted political strategies to sustain credibility, maintain political relevance, and frame the loss as part of an ongoing moral–democratic struggle. The sequential pattern—rejecting the results, criticising the process, and accepting with objections—enabled both leaders to navigate the political transition without losing support. The analysis also reveals that their rhetorical choices were influenced by Asian and Muslim cultural values, particularly collectivism, social harmony, and saving face. This study contributes to political communication scholarship and offers practical implications for reducing post-election polarization in culturally collectivist contexts.